2017
DOI: 10.4209/aaqr.2017.05.0177
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Deposition of Polychlorinated Dibenzo-p-dioxins and Dibenzofurans in Two Cities of Southern China

Abstract: Atmospheric deposition is an important pathway for air pollutants entering the environment. In order to better understand both dry and wet deposition of PCDD/Fs in ambient air, two cities -Guangzhou and Nanjing in Southern China, were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Dry deposition is one of the main ways for air pollutants to enter the ecosystem (Mi et al, 2012). The dry deposition of PCDD/Fs is the sum of deposition in the gas phase and particle phase (Zhu et al, 2017). Ambient air temperature, wind direction, particle size and other factors also affect the atmospheric deposition process (Wu et al, 2009;Chi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Dry deposition is one of the main ways for air pollutants to enter the ecosystem (Mi et al, 2012). The dry deposition of PCDD/Fs is the sum of deposition in the gas phase and particle phase (Zhu et al, 2017). Ambient air temperature, wind direction, particle size and other factors also affect the atmospheric deposition process (Wu et al, 2009;Chi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Physically dioxin has a small density of 1.8 g/cm 3 while NO2 gas is 1.45 g/cm 3 and SO2 is 2.63x10 -3 g/cm 3 but dioxin can be classified in non-gas particles. Dioxin is chemically classified as inactive (non-decay) and undergoes dry deposition (particles that fall to the ground) at a speed of about 0.2-0.5 cm/s in Greece (Olie et al, 1977), 0.27-0.28 (coastal), 0.19-0.24 (mountain), 0.148-0.162 (industrial estate), 0.49-0.98 (urban) in Taiwan (Chandra et al, 2015, Lee et al, 2016, Zhu et al, 2017. For dioxins in the atmosphere, dry deposition is more dominant than wet deposition (Wu et al, 2009, Huang et al, 2011, Chandra et al, 2015, Lee et al, 2016.…”
Section: The Concept Of Atmospheric Dispersion Of Dioxinmentioning
confidence: 99%
“…To avoid future contamination risks, such fly ash cannot be dumped directly into the landfill without proper treatment (McKay, 2002;Yang et al, 2007). Various studies have shown high concentration of such chlorinated compounds released into the environment from industrial activities and vehicular emissions (Tang et al, 2017;Xing et al, 2017;Zhu et al, 2017;Lee et al, 2018;Zhao et al, 2018). Mechanical treatment (MC), as an effective PCDD/F and PCB destruction technique has been employed to control emissions of persistent organic pollutants (Cheruiyot et al, 2019).…”
Section: Introductionmentioning
confidence: 99%